Detailed study of the CePd2-xNixAl3 magnetic phase diagram around its critical concentration - Sereni, J.G. (2006)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina